Pengaruh Sosial dan Nilai Harga terhadap Behavioral Intention to Use QRIS serta dampaknya pada Use Behavior: Studi Empiris pada UMKM Sektor Kuliner Kota Pekanbaru - Dyenda Azzahra; Ruhul Fitrios; Lila Anggraini (Jurnal Eksplorasi Akuntansi, 2024)
The presence of QRIS payment technology in the digitalization era shows that there is a level of technology adoption that originates from the intensity of behavior of MSME players as users of digital payment services. The aim of this research is to explore the role of social influence and price values on interest in using QRIS for MSMEs in the Culinary Sector in Pekanbaru City. This research uses quantitative descriptive methods. Empirical data was collected through questionnaires from 340 respondents who are MSME owners. Analyzed using SmartPLS 4.0 based on the SEM-PLS method. The research results concluded that social influence and price value influenced behavioral intentions to use QRIS, then behavioral intentions to use QRIS influenced usage behavior. Therefore, this study is consistent with the efforts of the government and Bank Indonesia to accelerate the implementation of digital payments in the development of the MSME digitalization program.